Wage inequality in Mexico expressed in economic dispersion of mandatory year-end bonus - Osorio Atondo, José Manuel (2021)
Income distribution within the economic, political, and social context of the national economies of countries has been examined in numerous and varied studies, showing wage inequality is one of the main factors negatively impacting development and growth.  This analysis shows the wage inequality evident in the economic dispersion of constitutionally mandated year-end bonuses (aguinaldo) to workers based on available data gathered in the National Household Income and Spending Survey (ENIGH, by its Spanish-language acronym) for the years 2015, 2016 and 2018. Employing a statistical processing methodology involving, description, and examination of data with the aid of Excel, specifically the Symbolab Math Solver, the study employs the Sturges rule, the Lorenz Curve and the Gini Index, which reveal inequality of the year-end bonus payment to Mexico's households in the years under study.